Minimal-invasive 3D laser printing of microimplants in organismo [data] - Afting, Cassian; Mainik, Philipp; Vázquez-Martel, Clara; Abele, Tobias; Kaul, Verena; Kale, Girish; Göpfrich, Kerstin; Lemke, Steffen; Blasco, Eva; Wittbrodt, Joachim (Universität, 2024)
Multi-photon 3D laser printing has gathered much attention in recent years as a means of manufacturing biocompatible scaffolds that can modify and guide cellular behavior in vitro. However, in vivo tissue engineering efforts have been limited so far to the implantation of beforehand 3D printed biocompatible scaffolds and in vivo bioprinting of tissue constructs from bioinks containing cells, biomolecules, and printable hydrogel formulations. Thus, a comprehensive 3D laser printing platform for in vivo and in situ manufacturing of microimplants raised from synthetic polymer-based inks is currently missing. Here we present a platform for minimal-invasive manufacturing of microimplants directly in the organism by one-photon photopolymerization and multi-photon 3D laser printing. Employing a commercially available elastomeric ink giving rise to biocompatible synthetic polymer-based microimplants, we demonstrate first applicational examples of biological responses to in situ printed microimplants in the teleost fish Oryzias latipes and in embryos of the fruit fly Drosophila melanogaster. This provides a framework for future studies addressing the suitability of inks for in vivo 3D manufacturing. Our platform bears great potential for the direct engineering of the intricate microarchitectures in a variety of tissues in model organisms and beyond.
Gefördert durch: Deutsche Forschungsgemeinschaft: EXC-2082/1-390761711
Gesehen am 24.06.2024
Keywords: Forschungsdaten; Datenbank